Pengaruh terapi fisik range of motion (rom) terhadap fungsi motorik ekstremitas pasien stroke - Panjaitan, Betty Yuliana; Anita, Fitri; Erwin, Tubagus (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Sudden interruption of blood flow to the brain and causing disability to paralysis is called a stroke. This problem can be overcome with physical therapy of Range Of Motion (ROM) in the form of physical exercises to increase mobility, muscle strength, prevent further complications. Purpose: To determine the effect of range of motion (ROM) physical therapy on the motor function of the extremities of stroke patients. Method: Quantitative research with quasi-experimental design using one group pre-post test. The number of samples was 21 respondents using purposive sampling technique in the Gedong Air Bandar Lampung Health Center Working Area from January 6 to February 7, 2025. Data were collected through pre- and post-intervention observation sheets with data analysis used was the Wilcoxon Test. Results: Quantitative research with quasi-experimental design using one group pre-post test. The number of samples was 21 respondents using purposive sampling technique in the Gedong Air Bandar Lampung Health Center Working Area from January 6 to February 7, 2025. Data were collected through pre- and post-intervention observation sheets with data analysis used was the Wilcoxon Test. Conclusion: The significance value is 0.000<0.05 and there is a significant difference between the level of extremity motor skills in stroke patients before being given intervention with a lower motor level and after being given there is an increase in motor skills. Keywords: Motor Function; ROM Therapy; Stroke. Pendahuluan: Terganggunya aliran darah ke otak secara tiba-tiba dan menyebabkan kecacatan hingga kelumpuhan disebut sebagai stroke. Permasalahan ini dapat diatasi dengan terapi fisik rentang gerak Range Of Motion (ROM) berupa latihan fisik dalam meningkatkan mobilitas, kekuatan otot, mencegah komplikasi lanjut. Tujuan: Untuk mengetahui pengaruh terapi fisik range of motion (rom) terhadap fungsi motorik ekstremitas pasien stroke. Metode: Penelitian kuantitatif dengan desain quasi experimental menggunakan one group pre-post test. Jumlah Sampel 21 responden dengan menggunakan teknik purposive sampling di Wilayah Kerja Puskesmas Gedong Air Bandar Lampung dari tanggal 6 Januari sampai 7 Februari 2025. Data dikumpulkan melalui lembar observasi pre dan post pemberian intervensi dengan analisis data yang digunakan adalah Uji Wilcoxon. Hasil: Nilai signifikansi 0.000<0,05 dan terlihat adanya perbedaan yang signifikan antara tingkat motorik ekstremitas pada pasien stroke sebelum diberikan intervensi dengan tingkat motorik lebih rendah dan setelah diberikan terdapat peningkatan motorik. Simpulan: Terapi fisik range of motion berpengaruh terhadap fungsi motorik ekstremitas pasien stroke di Wilayah Kerja Puskesmas Gedong Air. Kata kunci: Fungsi Motorik; Stroke; Terapi ROM.